Nuclear organization and gene expression - Spector, David (Henry Stewart Talks, 2007)
Current understanding of the organization of the mammalian cell nucleus and how this organization impacts on gene expression, in-vivo studies of gene expression as a result of the concerted processes of transcription, mRNA processing, messenger ribonucleoprotein particle (mRNP) export and translation, studies of spatial and temporal aspects of critical cellular processes within the context of the living cell, development of a cell system that allows the visualization of a transcription site and its mRNA and protein products directly in living cells, evaluation of spatial and temporal changes in chromatin structure, mRNA synthesis and factor association/disassociation during the transition from a transcriptionally inactive to an active state, understanding of the in-vivo dynamics of gene expression will provide the basis from which to elucidate spatial and/or temporal alterations that occur in cells associated with various disease states
Archived at 2018/05/31